2019
DOI: 10.18196/ijnp.3193
|View full text |Cite
|
Sign up to set email alerts
|

Nurse’ Knowledge and Their Performance on Cardiopulmonary Resucitation (CPR) in Critical and Emergency Care Unit

Abstract: Background: Knowing the important relation between knowledge and skill is important because it reflexes the action that nurses do to save people life. Objective: This research aimed to determine the relationship between the nurse's knowledge level and their performance on cardiopulmonary resuscitation in critical and emergency care unit. Method: The study was quantitative descriptive with the crosssectional design used sequential sampling with 30 nurses in critical and emergency care unit. The data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…A number of research studies currently demonstrating the relationship between the nurses' knowledge and their performance in CPR shows that, despite the increased search for updates, courses and training, knowledge of this topic is still low, and training and routine assessment can be useful to increase nurses' cognitive ability, which occurs more frequently in the hospital environment. [21][22] The articulation of active educational strategies to improve the teaching and learning process of CPR with BLS in adults adopted in this study indicated statistically significant results, which are also demonstrated in other research studies in Nursing. [20][21][22][23] Inverted classrooms can be thought as learning outside the classroom environment, characterized by activities performed before and after class, made possible by the regular and systematic use of interactive technologies in the teaching and learning process.…”
Section: /14supporting
confidence: 79%
See 1 more Smart Citation
“…A number of research studies currently demonstrating the relationship between the nurses' knowledge and their performance in CPR shows that, despite the increased search for updates, courses and training, knowledge of this topic is still low, and training and routine assessment can be useful to increase nurses' cognitive ability, which occurs more frequently in the hospital environment. [21][22] The articulation of active educational strategies to improve the teaching and learning process of CPR with BLS in adults adopted in this study indicated statistically significant results, which are also demonstrated in other research studies in Nursing. [20][21][22][23] Inverted classrooms can be thought as learning outside the classroom environment, characterized by activities performed before and after class, made possible by the regular and systematic use of interactive technologies in the teaching and learning process.…”
Section: /14supporting
confidence: 79%
“…[21][22] The articulation of active educational strategies to improve the teaching and learning process of CPR with BLS in adults adopted in this study indicated statistically significant results, which are also demonstrated in other research studies in Nursing. [20][21][22][23] Inverted classrooms can be thought as learning outside the classroom environment, characterized by activities performed before and after class, made possible by the regular and systematic use of interactive technologies in the teaching and learning process. 11 In this study, the inverted classroom strategy was characterized by sending educational materials and video lessons on the proposed theme, with the intention of directing previous study and providing a virtual facilitating mechanism that would complement the participants' teaching and learning process.…”
Section: /14supporting
confidence: 79%
“…In this context, we conducted an expanded study based on the theory of planned behaviour (TPB; Ajzen, 1991)-which states that human behaviour is determined by intention-using perceived benefits and risks of family presence and CPR self-confidence during family presence as anticipated predictors. Examining nurses' intention to allow FPDR is meaningful because nurses closely work with patients and a large number of nurses are often involved in resuscitation compared with other healthcare providers (Andriyani et al, 2019). There have been no studies that use TPB to expound the behaviour of nurses in the context of allowing FPDR in South Korea.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The more knowledge nurses have, the better performance they have. Routine training and evaluation may be useful to increase nurses' knowledge and skills [19].…”
Section: Resultsmentioning
confidence: 99%